THE PROSPECTS OF CREATION OF A MODIFIED INSULATING INORGANIC MATERIAL BASED ON SILICA AND ALUMINA MATERIAL - Pshinko, O. M.; Krasnyuk, A. V.; Grebennikov, V. M.; Shcherbak, A. S. (Science and Transport Progress, 2009)
In the article the analysis of use of heat insulation materials inUkraineis given. The advantages of creation of heat insulation inorganic material on the basis of aluminum silicate raw material compared to the heat insulation materials utilized today are shown.